2002
DOI: 10.1007/s00213-002-1172-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amantadine and bromocriptine on startle and sensorimotor gating: parametric studies and cross-species comparisons

Abstract: Amantadine modifies prepulse effects on startle in rats and humans, and disrupts prepulse effects on perceived stimulus intensity in humans; bromocriptine has clear effects on PPI in rats, but not in humans. The divergent effects of amantadine on sensorimotor and sensory effects of prepulses may reflect a divergence of brain circuitry regulating these processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 62 publications
6
44
3
Order By: Relevance
“…In previous reports in HS, acute exposure to NMDA antagonists led to greater levels of both PPI (Duncan et al, 2001;Abel et al, 2003;Swerdlow et al, 2002bSwerdlow et al, , 2009 and-in the case of memantine-MMN (Korostenskaja et al, 2007), but the present findings provide the first evidence for such effects in CPD patients. Conceivably, NMDA activity might be deficient within substrates responsible for core CPD symptoms, but be normal or even elevated in other brain regions regulating PPI and MMN.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In previous reports in HS, acute exposure to NMDA antagonists led to greater levels of both PPI (Duncan et al, 2001;Abel et al, 2003;Swerdlow et al, 2002bSwerdlow et al, , 2009 and-in the case of memantine-MMN (Korostenskaja et al, 2007), but the present findings provide the first evidence for such effects in CPD patients. Conceivably, NMDA activity might be deficient within substrates responsible for core CPD symptoms, but be normal or even elevated in other brain regions regulating PPI and MMN.…”
Section: Discussioncontrasting
confidence: 53%
“…Interestingly, whereas NMDA systems have been implicated in the regulation of both PPI and MMN, the evidence linking reduced NMDA activity to deficits in PPI and/or MMN is not entirely straightforward. Thus, PPI is actually increased in healthy subjects (HS) by NMDA antagonists such as ketamine (Duncan et al, 2001;Abel et al, 2003), the low-to moderate-affinity NMDAreceptor antagonist, memantine (Swerdlow et al, 2009), and by the mixed NMDA antagonist/dopamine agonist, amantadine (Swerdlow et al, 2002b). Although MMN has been reported to be reduced in HS by ketamine (Umbricht et al, 2000;Umbricht et al, 2002), it has also been shown to be increased by memantine (Korostenskaja et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While NMDA antagonists are generally reported to disrupt PPI in rodents, PPI is actually increased in healthy subjects (HS) by NMDA antagonists such as ketamine (Duncan et al 2001;Abel et al 2003) and by the mixed NMDA antagonist/dopamine agonist, amantadine (Swerdlow et al 2002). In intact rats, we detected PPI-enhancing effects of memantine, using relatively short (10-30 ms) prepulse intervals (Swerdlow et al 2009).…”
Section: Drug-enhanced Ppi As a Biomarker For Pact?mentioning
confidence: 84%
“…Alternatively, as reported in animals (Martin-Iverson and Else, 2000;Swerdlow et al, 2001Swerdlow et al, , 2002b and as discussed for the serotonin section, inconsistencies may be related, in part, to differences in PPI stimulus parameters including lead intervals and their sensitivity to dopaminergic modulation. Furthermore, there is increasing evidence that the effects of dopaminergic drugs on PPI may be related to baseline PPI, with greater reductions reported in subjects with high baseline PPI (Bitsios et al, 2005;Giakoumaki et al, 2007).…”
Section: Dopamine Depletionmentioning
confidence: 92%